Visible-light-driven photocatalytic degradation of diclofenac by carbon quantum dots modified porous g-C3N4: Mechanisms, degradation pathway and DFT calculation - Liu, Wen; Yunyi Li; Fuyang Liu; Wei Jiang; Dandan Zhang; Jialiang Liang (Water Research, 2019)
Metal-free photocatalysts have attracted growing concern in recent years. In this work, a new class of carbon quantum dots (CQDs) modified porous graphitic carbon nitride (g-C3N4) is synthesized via a facile polymerization method. With the optimal CQDs loading, the CQDs modified g-C3N4 exhibits ∼15 times higher degradation kinetic towards diclofenac (DCF) than that of pure g-C3N4. The enhanced photocatalytic activity can be ascribed to the improved separation of charge carriers as well as the tuned band structure. Moreover, a photosensitation-like mechanism is proposed to elucidate the photo-generated electrons transfer and reactive radicals formation. CQDs are anchored to g-C3N4 surface via CO bond, which provide channels for the preferential transfer of photo-excited electrons on DCF molecule to the conduction band of g-C3N4. Superoxide radical (·O2−) dominates the degradation of DCF, while holes (h+) show a negligible contribution. Density functional theory (DFT) calculation successfully predicts that the sites on DCF molecule with high Fukui index (f0) are preferable to be attacked by radicals. DCF degradation pathway mainly includes ring hydroxylation, ring closure and CN bond cleavage processes. Acute toxicity estimation indicates the formation of less toxic intermediates/products compared to DCF after photocatalysis. Moreover, the hybrid photocatalysts exhibit good reusability in five consecutive cycles. This work not only proposes a deep insight into photosensitation-like mechanism in the photocatalysis system by using C3N4-based materials, but also develops new photocatalysts for potential application on removal of emerging organic pollutants from waters and wastewaters.
Keywords: Carbon nitride; Carbon quantum dots; Diclofenac; Photocatalytic degradation; Visible light